2002
DOI: 10.1097/01.asn.0000019642.55998.69
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Nef Induces Proliferation and Anchorage-Independent Growth in Podocytes

Abstract: Abstract. HIV-associated nephropathy (HIVAN) is now the third leading cause of end-stage renal disease in the African American population. HIV-1 infects renal tubular and glomerular epithelial cells or podocytes, cells that are a critical part of the filtration barrier. HIV-1 infection induces the loss of podocyte differentiation markers and increases podocyte proliferation. It has been previously shown that HIV-infection induces loss of contact inhibition. Here, the HIV-1 gene responsible for proliferative ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
143
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(145 citation statements)
references
References 38 publications
1
143
1
Order By: Relevance
“…These cells proliferate under permissive conditions (gamma interferon at 33°C) but differentiate under nonpermissive conditions (37°C). The HIV-1 constructs have been described previously (17). Expression of HIV-1 genes was confirmed by immunoblot analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells proliferate under permissive conditions (gamma interferon at 33°C) but differentiate under nonpermissive conditions (37°C). The HIV-1 constructs have been described previously (17). Expression of HIV-1 genes was confirmed by immunoblot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike most other glomerulopathies, HIVAN is characterized by proliferation and dedifferentiation of podocytes, which are glomerular visceral epithelial cells (3,4,17). Recently, we showed that the HIV-1 nef gene is the primary determinant of this unusual podocyte phenotype (17,36) and that Nef stimulates podocyte proliferation and dedifferentiation through the Src-dependent mitogenactivated protein kinase 1,2 (MAPK1,2) pathways (15). Increased MAPK1,2 phosphorylation is also observed in mouse and human kidney sections of HIVAN (15).…”
mentioning
confidence: 99%
“…28 The vpr, tat, and nef constructs as well as a control green fluorescence protein-containing construct and a Stat3 dominant negative mutant (a gift from Dr. C.M. Horvath, The Rockefeller University, New York, NY) were individually introduced into wild-type conditionally immortalized podocytes maintained at 33°C via nucleofection (Amaxa Biosystems, Cologne, Germany), and the cells were transferred to 37°C for 3 d. 29 The transfection efficiency was evaluated by fluorescence microscopy confirming 70 to 80% efficiency.…”
Section: Hiv-1 Constructsmentioning
confidence: 99%
“…The gag/pol and VSV.G envelope genes were provided in trans using pCMV R8.91 and pMD.G plasmids, respectively. [3,6] Infectious viral supernatants were produced by transient transfection of 293T cells using effectene transfection reagent (QIAGEN Inc.) according to the manufacturer's instructions. Viral supernatants were collected at 48 and 72 hrs post-transfection.…”
Section: Preparation Of Pseudotyped Virusesmentioning
confidence: 99%
“…[1][2][3][4][5] The latter is characterized by focal glomerulosclerosis and tubulointerstitial lesions. [6] Acute renal failure has frequently been reported as a result of tubular cell injury (apoptosis and necrosis) in HIV-1-infected patients.…”
Section: Introductionmentioning
confidence: 99%